Sarcoplasmic masses in the skeletal muscle of a stranded pigmy sperm whale (Kogia breviceps) - Sierra Pulpillo, Eva María; Espinosa De Los Monteros Y Zayas, Antonio; Fernández Rodríguez, Antonio Jesús; Arbelo Hernández, Manuel Antonio; Caballero Cansino, María José; Rivero Santana, Miguel Antonio; Herráez Thomas, Pedro Manuel (Journal of Wildlife Diseases, 2013)
We measured the abundance of sarcoplasmic masses within skeletal muscle myocytes of an adult female stranded pigmy sperm whale (Kogia breviceps). The presence of these masses in other species has been reported in association with myopathies, including myotonic dystrophy, the most frequently related pathology. Other histopathologic muscle changes included a high number of internal nuclei, variations in fiber size and shape, and the predominance of type I fibers. 683 679 0,763 1,305 Q2 Q2 SCIE